2016
DOI: 10.1097/01.jaa.0000480569.39885.c8
|View full text |Cite
|
Sign up to set email alerts
|

Perceived efficacy and utility of postgraduate physician assistant training programs

Abstract: Completion of a postgraduate PA program is an alternative to on-the-job training. Graduates perceived that the benefits from these programs include increased competitiveness in the job market, decreased onboarding time, and overall enhancement of their professional careers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…27 APPs who have completed fellowships feel more confident and able to succeed in their field. 28 To this point, in one survey of hospitalist PAs, almost all reported that they would have been interested in completing a fellowship, even it meant a lower initial salary. 29 Despite having the same general goals and using similar national resources, our study reveals that APP fellows are trained and assessed very differently between programs.…”
Section: Discussionmentioning
confidence: 99%
“…27 APPs who have completed fellowships feel more confident and able to succeed in their field. 28 To this point, in one survey of hospitalist PAs, almost all reported that they would have been interested in completing a fellowship, even it meant a lower initial salary. 29 Despite having the same general goals and using similar national resources, our study reveals that APP fellows are trained and assessed very differently between programs.…”
Section: Discussionmentioning
confidence: 99%
“…Adding another trainee at the margin appears to require little more in the human resource office or in department commitment [ 6 ]. From the student’s viewpoint, additional education with supportive mentors provides more confidence that the graduate will be gainfully employed with a marketable skill set [ 15 ]. The economist views additional education as an opportunity cost [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adding another trainee appears to require little more in the human resource o ce or in department commitment (10). From the student's viewpoint, additional education with supportive mentors provides more con dence to be gainfully employed with a marketable skill set (11). The economist views additional education as an opportunity cost (12).…”
Section: Discussionmentioning
confidence: 99%